Analisis Kemampuan Penalaran Adaptif Siswa SMP dalam Menyelesaikan Soal Aritmatika Sosial - Oktaviana Safitri; Reni Astuti; Iwit Prihatin (LPD Universitas PGRI Pontianak, 2026)
Adaptive reasoning is one of the essential mathematical competencies that enables students to think logically, provide justification, draw conclusions, and evaluate mathematical arguments. However, many students still experience difficulties in applying adaptive reasoning when solving mathematical problems, particularly in the topic of social arithmetic. This study aimed to describe junior secondary school students' adaptive reasoning abilities in solving social arithmetic problems based on ability categories. The study employed a qualitative descriptive method with a case study approach. The research subjects consisted of three Year 7 students at SMP Kristen Ekklesia Kembayan, representing the high, moderate, and low ability categories. Data were collected through written tests and interviews. The instruments used were an adaptive reasoning test and interview guidelines. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings revealed that students in the high-ability category were able to fulfil all indicators of adaptive reasoning, namely making conjectures, providing reasons or evidence, drawing conclusions, examining the validity of arguments, and identifying mathematical patterns. Students in the moderate-ability category generally fulfilled most of the indicators but still encountered difficulties in providing complete mathematical justifications. Meanwhile, students in the low-ability category were unable to fulfil the indicators consistently due to misconceptions and difficulties in explaining the reasons underlying their answers. Therefore, adaptive reasoning skills need to be developed through learning activities that encourage students to provide explanations, justifications, and mathematical arguments. Keywords: adaptive reasoning, social arithmetic, junior secondary school students, qualitative study.